Faculty perceptions towards student library use in the International Islamic University Malaysia - Adikata, Adnan Ali (International Islamic University Malaysia, 1999)
The purpose of this study was to investigate faculty members' perceptions towards student libraryh use. The study was designed to identify the level of importance faculty members place on student library use and libraryh-based assignments. It also examined the roles and responsibilities of the faculty members and librarians in giding and supporting student library use as perceived by the respondents. An adapted survey instrument was administered to all faculty members at the departments of Usuluddin and Comparative religion, Qur'an and Sunnah and Fiqh and Usul al-Fiqh. The Statistical Package for Social Sciences was used to analyse the data. The findings reveal that faculty members felt that student library use is essential in enticing students' intellectual intelligence, increasing self-esteem and self-confidence, familiarising them with literature in their fields of study and improving their general communication skills. The study reports that faculty members valued library-based assignments because they increase students' awareness of the worldview. They preferred library assignments to be designed for focus and survey courses. Although they trusted the students' use skills, the faculty members emphasised the importance of learning library use processes. It was also reported that it was part of the faculty members' roles and responsibilities to motivate students to want to use the library, desiign library-based assignments, and provide extra credits and graded assignments to students. They didi not regard designing library-bases assignments to be time consuming. However, they also felt that the librarian should help students learn how to find information, make them feel at home and ensure the availability of up-to information in the library. The study concludes by providing some recommendations and suggestions for further studies.